Firm Heterogeneity in Capital/Labor Ratios and Wage Inequality - Marco Leonardi (Institute for the Study of Labor (IZA), 2003)
This paper provides some empirical evidence and a theory of the relationship between residual wage inequality and the increasing dispersion of capital/labor ratios across firms. I document the increasing variance of capital/labor ratios across firms in the US labor market. I also show that the increase in the capital intensity variance across firms is associated with the increasing wage variance across workers. To explain this empirical fact, I adopt a search model where firms differ in their optimal capital investment. The decline in the relative price of equipment capital makes the firm distribution of capital/labor ratios more dispersed. In a frictional labor market, this force generates wage dispersion among identical workers. Simple calibration of the model indicates that the dispersion of capital/labor ratios can account for about one third of the total increase in residual wage inequality.
Keywords: J31; J21; 330; wage inequality; capital intensity; search models; Lohnstruktur; Branche; Faktorintensität; Arbeitsnachfrage; Arbeitsuche; Suchtheorie; Investition; Theorie; Vereinigte Staaten